A study on the deoxyribonucleic acid (DNA) identification act 2009 / Che Mohd Firdaus Che Soh ...[et al.] - Che Soh, Che Mohd Firdaus; Mohd Sidek, Eliza Safreen; Amiruddin, Fairuz Azhan; Mohd Nasir, Mohd Aiman Syafiq; Azmi, Mohd Aizat; Yaakap, Mohd Azzamuddin (2010)
The research conducted is on the DNA Identification Act 2009. It looks into the various issues surrounding the DNA Identification Act 2009 that may have implications on the general Malaysian public. The aim of the research is to identify the problems and defects of the DNA Identification Act 2009 and to propose necessary amendments and recommendations to overcome these problems and defects. Throughout the research, we discovered that there are several issues arising out of the said DNA Identification Act 2009. First, the police are given absolute power in storing and collecting DNA samples with no separation of powers or independent body to monitor them. Also under the Act, the Head of the DNA Databank has power to rectify the information stored in the database without being subject to allegations of tampering and this may lead to abuse. The third issue is that chemists have been given the privilege of being immune from any default or omission done by them, thus not making them liable for any negligent act during the processing of DNA samples. Also, the definition of chemist under the act is too wide and general. Finally, the Act allows for retrospective DNA sample to be taken from people who are currently serving their sentence, as it has retrospective effect. From the research, it is concluded that there are many improvements that can be made to the DNA Identification Act 2009. Thus, recommendations and amendments are suggested for the aforementioned issues to be resolved.